The Putative APSES Transcription Factor RgdA Governs Growth, Development, Toxigenesis, and Virulence in Aspergillus fumigatus - Jun, Sang-Cheol (mSphere, 2020)
The APSES transcription factor (TF) in Aspergillus species is known to govern diverse cellular processes, including growth, development, and secondary metabolism. Here, we investigated functions of the rgdA gene (Afu3g13920) encoding a putative APSES TF in the opportunistic human-pathogenic fungus Aspergillus fumigatus. The rgdA deletion resulted in significantly decreased hyphal growth and asexual sporulation. Consistently, transcript levels of the key asexual developmental regulators abaA, brlA, and wetA were decreased in the ΔrgdA mutant compared to those in the wild type (WT). Moreover, ΔrgdA resulted in reduced spore germination rates and elevated transcript levels of genes associated with conidium dormancy. The conidial cell wall hydrophobicity and architecture were changed, and levels of the RodA protein were decreased in the ΔrgdA mutant. Comparative transcriptomic analyses revealed that the ΔrgdA mutant showed higher mRNA levels of gliotoxin (GT)-biosynthetic genes and GT production. While the ΔrgdA mutant exhibited elevated production of GT, ΔrgdA strains showed reduced virulence in the mouse model. In addition, mRNA levels of genes associated with the cyclic AMP (cAMP)-protein kinase A (PKA) signaling pathway and the SakA mitogen-activated protein (MAP) kinase pathway were increased in the ΔrgdA mutant. In summary, RgdA plays multiple roles in governing growth, development, GT production, and virulence which may involve attenuation of PKA and SakA signaling. IMPORTANCE Immunocompromised patients are susceptible to infections with the opportunistic human-pathogenic fungus Aspergillus fumigatus. This fungus causes systemic infections such as invasive aspergillosis (IA), which is one of the most life-threatening fungal diseases. To control this serious disease, it is critical to identify new antifungal drug targets. In fungi, the transcriptional regulatory proteins of the APSES family play crucial roles in controlling various biological processes, including mating, asexual sporulation and dimorphic growth, and virulence traits. This study found that a putative APSES transcription factor, RgdA, regulates normal growth, asexual development, conidium germination, spore wall architecture and hydrophobicity, toxin production, and virulence in A. fumigatus. Better understanding the molecular mechanisms of RgdA in human-pathogenic fungi may reveal a novel antifungal target for future drug development.